Evaluasi Kesalahan Proyeksi Penduduk Tahun 2020 untuk Memproyeksikan Penduduk Tahun 2025 Provinsi Jawa Barat - Wildan; Yayat Karyana (Jurnal Riset Statistika, 2021)
Abstract. West Java Province is one of the largest provinces in Indonesia. Naturally, the population factor is one of the supports in terms of development. The confusion of a number of population data from various Ministries and Institutions become one of the causes of the non-optimal implementation of government policies. Therefore, this thesis will discuss the calculation of error evaluation population projections carried out using the projection method and projecting from the results of population projections to improve data accuracy which exists. The method used as a benchmark for calculating projections is mathematical method, component method and mixed method. The three methods this results in population projections for year t from the total population aspect, gender and age grouping. After the population projections are obtained, then see how much error the projection value is. In this problem, MALPE and MAPE are in charge of this projection error evaluation technique. There are 3 aspects that become a reference in the calculation of the projected evaluation, namely: other factors are fertility mortality and mobility. Assumption of fertility is measured from the numerical value birth age group (ASFR) and total fertility (TFR). Assumption of mortality what is seen is a table of 24 death levels, while the assumption of mobility or migration is seen from the ASNMR (Age Specific Net Migration Rate) number. Obtained the smallest error value by the MAPE technique is 5.4 in the component method that carried out by BPS and the projection results for West Java Province are 51,338,337 million souls with the component method. Abstrak. Provinsi Jawa Barat merupakan salah satu provinsi terbesar di Indonesia. Tentunya, dalam faktor penduduk menjadi salah satu penunjang dalam hal pembangunan. Kesimpangsiuran sejumlah data penduduk dari berbagai Kementerian dan Lembaga menjadi salah satu penyebab tidak optimalnya pelaksanaan kebijakan pemerintah. Oleh karena itu, skripsi ini akan dibahas mengenai perhitungan evaluasi kesalahan proyeksi penduduk yang dilakukan menggunakan metode proyeksi serta memproyeksikan dari hasil proyeksi penduduk guna memperbaiki keakuratan data yang ada. Metode yang digunakan sebagai tolak ukur menghitung proyeksi adalah metode matematik, metode komponen dan metode campuran. Ketiga metode tersebut menghasilkan proyeksi penduduk tahun ke t dari aspek total penduduk, jenis kelamin dan pengelompokan umur. Setelah proyeksi penduduk diperoleh, selanjutnya dilihat berapa besar kesalahan nilai proyeksi. Pada permasalahan ini, MALPE dan MAPE yang bertugas dalam teknik evaluasi kesalahan proyeksi ini. Terdapat 3 aspek yang menjadi acuan dalam perhitungan evaluasi proyeksi, antara lain fertilitas, mortalitas dan mobilitas. Asumsi fertalitas diukur dari nilai angka kelahiran kelompok umur (ASFR) dan total fertilitas (TFR). Asumsi mortalitas yang dilihat adalah tabel level kematian 24, sedangkan asumsi mobilitas atau migrasi dilihat dari angka ASNMR (Age Specific Net Migration Rate). Didapatkan nilai kesalahan terkecil oleh teknik MAPE sebesar 5,4 pada metode komponen yang dilakukan BPS dan hasil proyeksi untuk Provinsi Jawa Barat sebanyak 51.338.337 juta jiwa dengan metode komponen.